Meningkatkan Literasi Teknologi melalui Webinar Pintu Gerbang Menuju Digital - Hermansyah, Masud; Andita Prasetyo , Nur; Wahid, Abdul; Afreyna Fauziah, Difari; Muliawan, Agung (Institut Teknologi dan Sains Mandala, 2023)
In the ever-evolving digital era, technology has become a major driving force in social, economic and educational change. Information and communication technologies (ICTs) have changed the way people work, communicate, and learn. As technology advances, it is important for individuals to have sufficient technological literacy to be able to participate actively in a digital society. The aim of this webinar is to provide an in-depth understanding of digital technology and teach practical skills in using it wisely. This webinar presents a series of topics related to digital technology, including digital transformation of Internet of Things (IoT) Technology in the Industrial World, Information Security Culture, and Computer and Network Security. By using the Zoom Video Communications application, webinar participants can easily participate from their respective locations, thus enabling broad participation and more flexibility for students to learn about technology. This webinar succeeded in increasing high school and vocational students' interest in the field of technology, as well as opening their insights about various career opportunities in the digital era. In addition, students also become more aware of the importance of ethics and responsibility in using technology, and are aware of its impact on society.